PEDESTRIANS ' CROSSING PROBLEMS AT THE MANZESE FOOTBRIDGE AND PROPOSED MEASURES - Shariff, Ali A.; Tamba, Saidi A.; Mdimi, Azizi A. (Tanzania Journal of Engineering and Technology, 2018)
In its efforts to restore safety to pedestrians the Government of Tanzania constructed the Manzese Footbridge along the Morogoro road. The project cost was TShs. 46,300 Million at the price in year 1990. The bridge design was carried out in accordance with Road Bridge Design Manual published by Japan Road Association. Unfortunately, only one pedestrian bridge has been built in Dar es Salaam since 1991. Footbridges and underpasses have hundred percent potential of protecting the pedestrian ' s safety when the traffic stream being crossed is heavy. It is not known why this advantage is not fully utilized by pedestrians in Dar es Salaam city. The paper tries to find out the reasons behind this trend. A case study of the footbridge at Manzese and two neighbouring zebra crossings one on either side of the bridge were used. Experimental data of the number of pedestrians crossing at the bridge, Tip Top and Bakhresa zebra crossings at fifteen minute intervals were collected for five working days starting from 1200 to 1515hours. The average deviations of pedestrians crossing at Tip Top and Bakhresa from the bridge were analysed by means of a paired t-statistic to uncover the usage inadequacy of the crossing facilities. Manzese foot bridge quality was also analysed by the Five Point Likert Scale using five quality attribute sentences. A random sample of 165 people was used in the analysis. The t-statistic showed that the bridge crossing is not significant at 5% level but significant at Tip Top and Bakhresa zebra crossings. This reveals that the pedestrians are not using the bridge compared with the other two zebra crossings. The Likert method showed that inadequate security, loss of muscle energy, no plaza, dizziness and no facilities to attract crossing of all types of pedestrians are reasons hindering its use. It is recommended that the above findings can be rectified by providing security lighting, police patrol and modification of bridge structure.